A process for preparing a micro- and nano-structured composite substrate

CN122917686APending Publication Date: 2026-10-16DONGGUAN ZHANHONG ENVIRONMENTAL PROTECTION MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611353039.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明要解决的技术问题是克服现有软质TPU表面装饰工艺中图案精细度差、无立体微结构、油墨附着力弱、产品耐久性不足以及人工成本高的缺陷,提供一种能够在软质热塑性弹性体薄膜上制备高精度微纳米光学结构并将其与基材牢固复合的工艺

Benefits of technology

(1)图案精细度高。第一支撑保护膜和第二支撑保护膜交替撑着,软质薄膜在滚涂过程中不被拉伸,加上低收缩率的UV树脂,两面分别做出了高精度的微纳结构,精细度比平面印刷好得多。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917686A_ABST
    Figure CN122917686A_ABST
Patent Text Reader

Abstract

The application discloses a process for preparing a micro-nano structure composite substrate, and belongs to the technical field of surface decoration. The process comprises the following steps: first, performing corona treatment on a soft thermoplastic elastomer film, and then combining a first surface of the film with a first supporting protective film; second, performing roll coating of UV photoetching resin on a second surface of the film, and then curing the UV photoetching resin to form a micro-nano convex lens array layer; third, after the first supporting protective film is removed, adhering a second supporting protective film; fourth, performing roll coating of UV resin on the first surface to form a photoetching concave pattern layer, and then performing color wiping and printing of a base color, and then combining a transparent color adhesive layer; fifth, after the second supporting protective film is removed, applying a stain-proof layer on both surfaces and cutting; finally, removing the stain-proof layer on the adhesive layer side, and then performing hot pressing to combine the semi-finished product with a substrate, and then removing the stain-proof layer on the lens layer side. According to the application, the micro-nano convex lens array and the photoetching concave pattern are prepared on both surfaces of the film respectively, so that a three-dimensional decoration effect is realized, and the product has good tensile resistance, hydrolysis resistance and aging resistance, and can be applied to the fields of shoes, clothes, bags, mobile phone cases and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of surface decoration technology, specifically to a process for preparing micro-nano structures on soft thermoplastic elastomer films and compositing them with a substrate, which is particularly suitable for surface decoration of footwear, clothing, bags, artificial leather and genuine leather products. Background Technology

[0002] Currently, the common practice for surface decoration on soft TPU films is to directly screen print, digitally print, or heat transfer the film surface, then apply TPU hot melt adhesive, and finally hot press it onto artificial leather, fabric, or genuine leather.

[0003] This existing process has several obvious shortcomings.

[0004] First, the printed patterns lack three-dimensional microstructures; the ink is merely physically adsorbed onto the TPU surface, resulting in insufficient pattern precision and inadequate expressiveness for high-end decorative applications. Second, the absence of micro / nano textures prevents the creation of visual effects such as three-dimensional suspension, depth of field, or flowing light, leading to a limited decorative effect. Third, the lack of a locking design for micro / nano structures makes it difficult to simultaneously maintain precision and durability on flexible substrates. Fourth, existing products do not adequately meet the requirements of high-end footwear and apparel in terms of tensile strength, bending resistance, hydrolysis resistance, washability, abrasion resistance, yellowing resistance, and weather resistance. Fifth, the footwear and apparel industry currently relies heavily on sewing to fix decorative components, resulting in high labor costs.

[0005] To address these issues, this invention proposes a process for preparing micro / nano-structured composite substrates. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to overcome the defects of existing soft TPU surface decoration processes, such as poor pattern fineness, lack of three-dimensional microstructure, weak ink adhesion, insufficient product durability and high labor cost, and to provide a process that can prepare high-precision micro-nano optical structures on soft thermoplastic elastomer films and firmly bond them to the substrate.

[0007] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, a process for preparing micro / nano-structured composite substrates includes the following steps: S1 Pretreatment: The film undergoes corona treatment, and then the first surface of the film is laminated and fixed with a first supporting protective film. The film is a soft thermoplastic elastomer. Corona treatment introduces polar groups such as hydroxyl and carbonyl groups onto the film surface through high-voltage discharge, increasing the surface energy from approximately 30 mN / m to over 42 mN / m. This changes the film surface from hydrophobic to hydrophilic, thereby enhancing the adhesion of UV lithography resin and subsequent inks, and upgrading the bonding method between the ink and the film from physical adsorption to chemical bonding. The first supporting protective film (low-viscosity PET film) is laminated onto the first surface of the film, providing rigid support for subsequent roller coating on the second surface. Because the soft TPU film is inherently flexible, it is prone to stretching deformation under roller coating pressure. If the film is stretched, the size of the subsequently formed micro / nano structures will deviate from the design value, and the optical effect cannot be guaranteed. The presence of the first supporting protective film disperses and bears the roller coating pressure, ensuring the film maintains dimensional stability during processing and guaranteeing the forming accuracy of the micro / nano structures.

[0008] In S1, the soft thermoplastic elastomer can be a TPU or PVC transparent film. As one implementation, a TPU film with a hardness of 75A to 95A and a thickness of 0.1 to 2.0 mm, preferably 0.1 to 0.8 mm, is used. The corona treatment power is 6 kW to 15 kW, and the treatment speed is 10 to 60 m / min, resulting in a surface energy of 42 mN / m or higher after treatment. This power and speed range ensures sufficient treatment strength on the film surface. If the power is too low or the speed is too high, the discharge energy received per unit area of ​​the film is insufficient, leading to inadequate generation of surface polar groups and a surface energy below 42 mN / m. Conversely, if the power is too high or the speed is too slow, overtreatment may result in an excessively thick oxide layer on the film surface, negatively impacting subsequent adhesion. Only after the surface energy reaches 42 mN / m or higher can the UV photolithography resin and subsequent inks form good wetting and adhesion on the film.

[0009] S2 Formation of a Micro / Nano Lens Array: UV photolithography resin is rolled onto the second surface of the thin film and cured by UV lamp irradiation, forming a micro / nano lens array layer on the second surface of the thin film. Then, the first support protective film composited in step S1 is removed, and a second support protective film is attached to the cured micro / nano lens array layer for fixation. During the roll coating process, the UV photolithography resin replicates the corresponding micro / nano lens array pattern on the thin film surface by contacting the micro / nano structure mold (the concave and convex structure of the roller surface). Subsequently, UV lamp irradiation causes the photoinitiator in the resin to absorb light energy and generate free radicals, initiating a polymerization reaction, and the resin changes from a liquid state to a solid state, fixing the lens structure. The first support protective film provides support for the roll coating in S1, preventing the thin film from being stretched and deformed. After the lens is cured, this protective film is removed, and the second support protective film is attached to the lens surface to protect the formed lens layer and prevent damage during the subsequent concave pattern roll coating process in S3. The two support protective films are used alternately, providing support for the thin film at different stages, realizing the locking of the micro / nano structure on the flexible thin film.

[0010] In S2, the UV lithography resin is polyurethane acrylate with an elongation at break of over 150% and a volume shrinkage rate of less than 8%. Elongation at break is a critical indicator; if it is below 150%, the cured resin layer cannot keep up with the deformation during film bending and stretching, easily leading to microcracks or even complete cracking. If the lens structure is damaged, the optical effect will be lost. If the volume shrinkage rate is above 8%, the volume change during curing is too large, causing the lens's radius of curvature and height to deviate, and the refraction and diffraction effects of light will not meet expectations.

[0011] In S2, the wet film thickness for roller coating is 8 μm to 30 μm, and the roller coating speed is 5 m / min to 20 m / min. If the wet film is too thin (below 8 μm), the lens height will be insufficient after curing, resulting in weak optical modulation effect; if it is too thick (above 30 μm), the corresponding curing shrinkage internal stress will be large, which may cause the film to warp and the lens array to deform. If the roller coating speed is too fast, the coating will be uneven; if it is too slow, the efficiency will be affected.

[0012] In S2, the UV curing wavelength is 395nm, the light intensity is 300mJ / cm, and the irradiation distance is 5cm to 15cm. The 395nm wavelength allows the photoinitiator in the polyurethane acrylate to effectively absorb light energy and generate free radicals, initiating the polymerization reaction. A light intensity of 300mJ / cm ensures the resin cures completely within a reasonable time; too low an intensity results in insufficient curing and a sticky surface, while too high an intensity leads to surface curing before the interior is properly cured. An irradiation distance of 5cm to 15cm ensures a suitable energy density reaching the resin surface; too close may cause localized overheating, while too far results in excessive light intensity attenuation.

[0013] In S2, the fabricated micro / nano convex lens array layer has a lens diameter of 10m–50m and a lens height of 5m–20m. Within this range, the convex lens array can produce effective diffraction and refraction effects in the visible light band (380nm–780nm). If the diameter is too small (<10m), manufacturing precision is difficult to guarantee, and excessive diffraction will cause color dispersion; if the diameter is too large (>50m), it becomes almost visible to the naked eye, weakening the light-glowing effect. The same applies to the height: below 5m, the curvature is too small for sufficient light convergence; above 20m, the lens protrudes too much and is easily damaged in subsequent processes.

[0014] S3 Forming and Filling Photolithographic Recessed Patterns: UV photolithography resin is rolled onto the first surface of the film and cured by UV lamp irradiation to form a photolithographic recessed pattern layer on the first surface of the film; the photolithographic recessed pattern layer is rubbed with color, and then ink is used to print the base color on the first surface of the film, and an adhesive layer is laminated on the first surface of the film.

[0015] In S3, the color-rubbing process involves scraping and smearing the color. The color-rubbing agent is a mixture of alcohol and pigment, which dries quickly. The adhesive layer is a hot melt adhesive or a crosslinking agent. After the color-rubbing agent is applied to the entire first surface, the raised parts are scraped off with a scraper, leaving only the color-rubbing agent inside the grooves. Because the alcohol in the color-rubbing agent evaporates very quickly, the pigment is quickly fixed in the grooves, without time to diffuse outwards. Subsequently, ink is printed on the entire first surface, with the grooves covered by the color-rubbing layer, and the raised parts directly attached to the film surface, forming the background color. The color in the grooves contrasts with the background color, making the pattern clear and prominent. The adhesive layer is laminated on the recessed pattern layer and melts when heated during the subsequent S5 heat pressing process, bonding the decorative product to the substrate. The adhesive layer is a transparent or semi-transparent material to ensure that light can pass through the adhesive layer to reach the color layer of the recessed pattern and be reflected back, creating a visual effect. When the adhesive layer is a hot melt adhesive, the melting point is 80℃~160℃, the activation temperature is 90℃~125℃, and the application thickness is 0.1mm~0.2mm. The melting point and activation temperature are set within this range to ensure sufficient melting and wetting of the substrate surface at the S5 pressing temperature. If the melting point is too low, it is prone to softening during storage and transportation; if the melting point is too high, a higher pressing temperature is required to melt it, potentially exceeding the heat resistance range of TPU. The application thickness is 0.1 to 0.2 mm, ensuring adhesive strength without being too thick and affecting the feel and softness.

[0016] In S3, the groove depth of the photolithographic recessed pattern layer is 5m to 20m, and the groove width is 5m to 30m. If the groove is too shallow (<5m), the pigment cannot be retained, the saturation is insufficient, and it is easily worn through; if it is too deep (>20m), the wiping agent cannot fill to the bottom, and it is easy to form air bubbles or voids. If the width is too narrow, the pigment cannot enter; if it is too wide, the surface tension of the pigment cannot support it and it will overflow.

[0017] S4 Applying the Anti-fouling Layer and Cutting: Remove the second supporting protective film from step S2, apply a first anti-fouling layer to the side of the micro / nano lens array layer, and apply a second anti-fouling layer to the side of the adhesive layer. Then cut it into a preset shape and size to form a semi-finished product. The first anti-fouling layer is a transparent PET anti-fouling layer, and the second anti-fouling layer is a release film or honeycomb paper. After removing the second supporting protective film, the micro / nano lens array layer is exposed. Applying a transparent PET anti-fouling layer to the side of the micro / nano lens array layer protects it from scratches or contamination during cutting, storage, and transportation; the transparent material facilitates quality inspection during production. Applying a release film or honeycomb paper to the side of the adhesive layer protects the adhesive layer (hot melt adhesive) from contamination and adhesion to other items. Both anti-fouling layers are temporary protection and will be removed during subsequent use.

[0018] S5 Hot Press Lamination: Before hot pressing, the substrate to be hot pressed is cleaned and prepared, the second anti-fouling layer is removed, the semi-finished product is placed on the substrate, and hot pressing is performed under heating and pressure to laminate the semi-finished product with the substrate. Finally, the first anti-fouling layer is removed.

[0019] In S5, the heat pressing temperature is 140℃~220℃, the pressure is 10kg~35kg, and the time is 35 seconds~50 seconds. As one implementation method, the upper mold is 200℃~220℃, the lower mold is 80℃~120℃, the pressure is 25kg~30kg, and the time is 40 seconds. The heat pressing temperature of 140℃ to 220℃ is designed to ensure the hot melt adhesive is fully melted and activated (hot melt adhesive activation temperature 90~125℃) while preventing thermal deformation of the film and UV resin layer (TPU's Vicat softening point is generally 120~180℃). Too low a temperature will result in insufficient melting and poor adhesion of the hot melt adhesive, while too high a temperature will cause the film and micro / nano structures to soften and deform. The pressure of 10kg to 35kg allows the molten hot melt adhesive to penetrate into the microstructure of the substrate surface under pressure, forming a mechanical anchor. The time of 35 seconds to 50 seconds ensures that the hot melt adhesive has sufficient time to flow, wet, and penetrate in its molten state. The substrate can be fabric, artificial leather, or genuine leather.

[0020] In the first aspect, the optical coordination between the micro-nano convex lens array and the concave pattern: the micro-nano convex lens array layer is the optical layer visible to the finished product, and the photolithographic concave pattern layer is the colored pattern layer. They are disposed on opposite sides of the film. After the light is refracted by the convex lens, it illuminates the colored pattern, and the reflected light passes through the convex lens again to form a three-dimensional luminous visual effect.

[0021] Secondly, the present invention also provides a decorative article prepared according to the above process, comprising a substrate, an adhesive layer, a photolithographic recessed pattern layer, a thin film layer and a micro / nano convex lens array layer arranged sequentially from bottom to top, wherein the photolithographic recessed pattern is filled with a colorant and ink.

[0022] Compared with the existing technology, the present invention has the following main improvements: (1) High pattern precision. The first and second support protective films alternately support the soft film without stretching during the roll coating process. With the addition of UV resin with low shrinkage rate, high-precision micro-nano structures are made on both sides, and the precision is much better than that of planar printing.

[0023] (2) Unique optical effects. With the lens facing up and the color facing down, the light passes through the lens to the color layer and then reflects back to pass through the lens again. After two modulations, the effect of flowing light and three-dimensional suspension is stronger, and the pattern changes dynamically when the viewing angle changes.

[0024] (3) Color durability. The rubbing agent and ink are sandwiched between the film and the substrate, and do not directly contact the outer surface. They are not worn by daily friction, so the color lasts longer.

[0025] (4) Reliable locking. Two supporting protective films alternately support and lock the micro-nano structure on the flexible film, which not only ensures the molding accuracy, but also protects the molded structure from damage by subsequent processes.

[0026] (5) Good durability. The polyurethane acrylate UV resin used has high elongation at break and low shrinkage. Combined with polyurethane hot melt adhesive, it is resistant to stretching, hydrolysis and aging. It can meet the requirements of the footwear and apparel industry for tensile strength, bending, washing, abrasion resistance, yellowing and weather resistance.

[0027] (6) Save labor. Hot pressing replaces sewing, and decorative parts are formed by hot pressing in one go instead of sewing them one by one, which significantly reduces labor costs.

[0028] (7) Wide range of applications. It can be laminated onto fabrics, artificial leather, and genuine leather, and can be used in shoes, clothing, bags, and mobile phone cases. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the layered structure of this application.

[0030] In the figure: 1. Thin film; 2. Micro / nano convex lens array layer; 3. Photolithographic concave pattern layer; 4. Shaping layer; 5. Base color layer; 6. Adhesive layer; 7. Substrate. Detailed Implementation

[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] It should be noted that when a component is said to be mounted on another component, it can be directly mounted on the other component or may be interspersed with an intermediate component. When a component is said to be set on another component, it can be directly set on the other component or may also be interspersed with an intermediate component. When a component is said to be fixed to another component, it can be directly fixed to the other component or may also be interspersed with an intermediate component.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The terminology used herein includes any and all combinations of one or more of the associated listed items.

[0034] Example 1 In this embodiment, micro- and nanostructures are prepared on soft TPU and then composited with fabric.

[0035] S1 Pretreatment: Select TPU film 1 with a hardness of 85A and a thickness of 0.2mm. Perform corona treatment at a power of 10kW and a speed of 30m / min until the surface energy reaches above 42mN / m. Then, laminate and fix the first surface of TPU film 1 with a low-viscosity PET film with a thickness of 0.075mm under a pressure of 30kg.

[0036] S2 forms a micro / nano lens array: Polyurethane acrylate UV photolithography resin (elongation at break ≥150%, volume shrinkage ≤8%), wet film thickness 10 μm, roller coating speed 15 m / min, applied to the second surface of TPU film 1, UV cured at 395 nm wavelength, 300 mJ / cm light intensity, 5 cm irradiation distance, forming a micro / nano lens array layer 2 (lens diameter 20 μm, lens height 10 μm) on the second surface. The first supporting protective film on the first surface is peeled off, and a low-tack PET film is laminated onto the cured micro / nano lens array layer 2 as a second supporting protective film.

[0037] S3 forms and fills the photolithographic recessed pattern: The same UV photolithographic resin is rolled onto the first surface of the TPU film 1 and UV cured under the same conditions to form the photolithographic recessed pattern layer 3 (groove depth 10 μm, groove width 15 μm). A color-rubbing agent mixed with alcohol and pigment is used to scrape and smear the color to form a color-rubbing layer. Then, an ink base color layer is printed on the first surface. Finally, a translucent polyurethane hot melt adhesive (melting point 120℃, activation temperature 100℃, adhesive thickness 0.15 mm) is laminated onto the first surface.

[0038] S4 Applying the anti-fouling layer and cutting: Remove the second support protective film from the second surface, attach a transparent PET film as the first anti-fouling layer to the side of the micro-nano convex lens array layer 2, attach honeycomb paper as the second anti-fouling layer to the side of the adhesive layer, and cut it into a preset shape to form a semi-finished product.

[0039] S5 Hot Press Lamination: Clean and prepare the fabric to be laminated (1.2mm thick), remove the second anti-fouling layer (honeycomb paper), place the semi-finished product on the fabric with the first surface (adhesive layer side) facing down, press the upper mold at 210℃, the lower mold at 100℃, the pressure at 30kg, and press for 40 seconds to laminate the semi-finished product with the fabric, and finally remove the first anti-fouling layer (transparent PET film).

[0040] The decorative product produced in this embodiment consists of, from bottom to top, a fabric substrate 7, a polyurethane hot melt adhesive layer 6, a photolithographic recessed pattern layer 3 (filled with a rubbing layer 4 and a base color layer 5), a TPU film layer 1, and a micro / nano convex lens array layer 2. When viewed from different angles, it exhibits a very obvious flowing light effect and a three-dimensional floating feel. The edges of the rubbing pattern are clear, without any bleeding or blurring. The hot melt adhesive layer 6 adheres firmly to the fabric, without delamination or air bubbles.

[0041] Example 2 This embodiment involves fabricating micro / nano structures on soft TPU and then composited with artificial leather.

[0042] S1 Pretreatment: Select TPU film 1, hardness 90A, thickness 0.15mm. Corona treatment at 10kW power and 30m / min speed, achieving a surface energy of over 42mN / m. Then, the first surface is laminated and fixed with a 0.075mm thick low-viscosity PET film under 30kg pressure.

[0043] S2 forms a micro / nano convex lens array: same as in Example 1.

[0044] S3 Forming and filling photolithographic recesses: This is basically the same as in Example 1, except that the hot melt adhesive used is a low-temperature adhesive (activation temperature 1005°C).

[0045] S4 Apply antifouling layer and cut: Same as in Example 1.

[0046] S5 hot-press lamination: Clean and prepare the artificial leather (1.0mm thick) to be laminated, remove the second anti-fouling layer, place the semi-finished product on the artificial leather with the first surface facing down, press the upper mold at 200℃, the lower mold at 120℃, the pressure at 25kg, and heat for 40 seconds, and finally remove the first anti-fouling layer.

[0047] The product made in this embodiment has a distinct three-dimensional decorative effect, high pattern fineness, and vivid color contrast. The surface of artificial leather is relatively dense, allowing the low-temperature hot melt adhesive to fully melt at 180°C, resulting in a very strong bond.

[0048] Example 3 In this embodiment, micro-nano structures are prepared on soft TPU and then composited with dermal skin.

[0049] S1 Pretreatment: Select TPU film 1, hardness 85A, thickness 0.2mm. Corona treatment at 10kW power and 30m / min speed, achieving a surface energy of over 42mN / m. Then, the first surface is laminated and fixed with a 0.075mm thick low-viscosity PET film under 30kg pressure.

[0050] S2 forms a micro / nano convex lens array: same as in Example 1.

[0051] S3 forms and fills the photolithographic concave pattern: Same as Example 1.

[0052] S4 Apply antifouling layer and cut: Same as in Example 1.

[0053] S5 Hot Press Lamination: Clean and prepare the genuine leather (1.5mm thick) to be laminated, remove the second anti-fouling layer, place the semi-finished product on the genuine leather with the first surface facing down, press the upper mold at 200℃, the lower mold at 120℃, the pressure at 25kg, and press for 40 seconds. Finally, remove the first anti-fouling layer.

[0054] The product made in this embodiment has excellent optical effects. The lens layer adheres smoothly to the genuine leather surface without wrinkles or curling edges. The genuine leather surface itself has roughness and fiber pores. During the pressing process, the hot melt adhesive penetrates into the fiber gaps of the genuine leather surface, providing both mechanical anchoring and chemical bonding, resulting in a stronger bond than that of artificial leather and fabrics.

[0055] The three embodiments above used fabric, artificial leather, and genuine leather, respectively, verifying the applicability of this process to different substrates. The products produced by the three embodiments share several common features: the lens faces upwards and the color faces downwards, allowing light to pass through the lens twice, creating a flowing light effect and a three-dimensional suspension effect; the color layer is sandwiched between the film and the substrate, not directly exposed, resulting in good abrasion resistance; and the adhesive layer is firmly bonded to the substrate without delamination. The only difference between the three embodiments lies in the adjustment of the substrate type and the heat pressing temperature, demonstrating the excellent adaptability of this process to different substrates.

[0056] The following commercial brands are applicable in the above embodiments: TPU film: BASF Elastollan 1185A, hardness 85A / 90A, thickness 0.15 / 0.2mm; PET support protective film: 0.075mm low-tack PET, peel strength 30g / 25mm; UV lithography resin (lens / groove universal): BASF 6202 aliphatic polyurethane acrylate, elongation at break 165%, volume shrinkage 6.2%; Colorant: Seiko 3700 series alcohol-soluble color paste; Mild solvent ink: Roland SOLJET ES3 four-color ink; Polyurethane hot melt adhesive: Huntsman Pearlstick 34-581, melting point 120℃, activation temperature 100℃; First-class anti-fouling PET: 0.05mm transparent low-peel PET, peel force 10g / 25mm; 8. Second anti-fouling honeycomb paper: 80g / m², thickness 0.3mm.

[0057] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0058] Those skilled in the art should recognize that the above embodiments are merely illustrative of the present invention and are not intended to limit the present invention. Any appropriate changes and variations made to the above embodiments within the essential spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A process for preparing micro / nano-structured composite substrates, characterized in that, Includes the following steps: S1 Pretreatment: The film is subjected to corona treatment, and then the first surface of the film is bonded and fixed with the first support protective film, wherein the film is a soft thermoplastic elastomer; S2 Formation of micro / nano convex lens array: UV photolithography resin is rolled onto the second surface of the film and cured by UV lamp to form a micro / nano convex lens array layer on the second surface of the film; then the first support protective film composited in step S1 is removed, and the second support protective film is attached to the cured micro / nano convex lens array layer for fixation. S3 Forming and filling photolithographic recessed patterns: UV photolithography resin is rolled onto the first surface of the film and cured by UV lamp irradiation to form a photolithographic recessed pattern layer on the first surface of the film. Color wiping is performed on the photolithographic recessed pattern layer, and then ink is used to print the base color on the first surface of the film. An adhesive layer is then laminated on the first surface of the film. S4 Applying antifouling layer and cutting: Remove the second support protective film in step S2, apply the first antifouling layer to the side of the micro-nano convex lens array layer, apply the second antifouling layer to the side of the adhesive layer, and then cut it into a preset shape and size to form a semi-finished product; S5 Hot Press Transfer: Before hot pressing, the substrate to be hot pressed is cleaned and prepared, the second anti-fouling layer is removed, the semi-finished product is placed on the substrate, and hot pressing is performed under heating and pressure to bond the semi-finished product with the substrate. Finally, the first anti-fouling layer is removed.

2. The process according to claim 1, characterized in that, In step S1: the soft thermoplastic elastomer is one of TPU or PVC transparent film; and / or, The power of the corona treatment is 6kW to 15kW, the treatment speed is 10 to 60m / min, and the surface energy after treatment reaches more than 42mN / m.

3. The process according to claim 2, characterized in that, The soft thermoplastic elastomer is a TPU film with a hardness of 75A to 95A and a thickness of 0.1 to 2.0 mm.

4. The process according to claim 1, characterized in that, The UV photolithography resin mentioned in steps S2 and S3 is polyurethane acrylate, with an elongation at break of more than 150% and a volume shrinkage rate of less than 8%.

5. The process according to claim 1, characterized in that, In step S2, the wet film thickness of the roller coating is 8 μm to 30 μm, and the roller coating speed is 5 m / min to 20 m / min; and / or, The UV curing wavelength is 395nm, the light intensity is 300mJ / cm, and the irradiation distance is 5cm to 15cm; and / or, The lens diameter of the micro / nano convex lens array layer is 10m to 50m, and the lens height is 5m to 20m.

6. The process according to claim 1, characterized in that, In step S3, the color-rubbing process involves scraping and applying color, and the color-rubbing agent is a mixture of alcohol and pigment; and / or, The adhesive layer is a hot melt adhesive with a melting point of 80℃~160℃, an activation temperature of 90℃~125℃, and an application thickness of 0.1mm~0.2mm.

7. The process according to claim 1, characterized in that, In step S5, the pressing temperature is 140℃~220℃, the pressure is 10kg~35kg, and the time is 35 seconds~50 seconds.

8. The process according to claim 7, characterized in that, The pressing temperature is 200℃~220℃ for the upper mold and 80℃~120℃ for the lower mold, the pressure is 25kg~30kg, and the time is 40 seconds.

9. The process according to claim 1, characterized in that, The substrate mentioned in step S5 is fabric, artificial leather, or genuine leather.

10. The process according to claim 1, characterized in that, In step S4, the first antifouling layer is a transparent PET film; the second antifouling layer is a release film or honeycomb paper.

11. The decorative article prepared according to any one of claims 1 to 10, characterized in that, It includes, from bottom to top, a substrate, an adhesive layer, a photolithographic pattern layer, a thin film layer, and a micro / nano convex lens array layer, wherein the photolithographic pattern layer is filled with a colorant and ink.